Cultural Imperialism and Popular Culture: Unveiling the Influence of Salmah Ismail @ Saloma in the Federation of Malaya - Mohd Firdaus Abdullah (Tanjung Malim, 2023)
Cultural Imperialism and Popular Culture: Unveiling the Influence of Salmah Ismail @ Saloma in the Federation of Malaya by Mohd Firdaus Abdullah